Structural changes and enzymatic response of Napier grass (Pennisetum purpureum) stem induced by alkaline pretreatment. (October 2016) - Phitsuwan, Paripok; Sakka, Kazuo; Ratanakhanokchai, Khanok
Graphical abstract: Highlights: Napier grass (NP) is a promising energy crop in the tropical region. Four industrially feasible alkaline pretreatments were tested on NP stem. Relationship of its structural changes and digestibility was clearly demonstrated. Porosity formation and lignin reduction increased enzymatic digestibility of NP. NaOH pretreatment was the best for glucose production (94% yield). Abstract: Napier grass is a promising energy crop in the tropical region. Feasible alkaline pretreatment technologies, including NaOH, Ca(OH)2, NH3, and alkaline H2 O2 (aH2 O2 ), were used to delignify lignocellulose with the aim of improving glucose recovery from Napier grass stem cellulose via enzymatic saccharification. The influences of the pretreatments on structural alterations were examined using SEM, FTIR, XRD, and TGA, and the relationships between these changes and the enzymatic digestibility of cellulose were addressed. The extensive removal of lignin (84%) in NaOH-pretreated fibre agreed well with the high glucan conversion rate (94%) by enzymatic hydrolysis, while the conversion rates for fibre pretreated with Ca(OH)2, NH3, and aH2 O2 approached 60%, 51%, and 42%, respectively. The substantial solubilisation of lignin created porosity, allowing increased cellulose accessibility to cellulases in NaOH-pretreated fibre. In contrast, high lignin content, lignin redeposition on the surface, and residual internal lignin and hemicellulose impeded enzymatic performance in Ca(OH)2 -, NH3 -, and aH2 O2 -pretreated fibres, respectively.